A cross-linguistic, sound symbolic relationship between labial consonants, voiced plosives, and Pokémon friendship - Kilpatrick, Alexander; Ćwiek, Aleksandra; Lewis, Eleanor; Kawahara, Shigeto (Frontiers in Psychology, 2023)
This paper presents a cross-linguistic study of sound symbolism, analysing a six-language corpus of all Pokémon names available as of January 2022. It tests the effects of bilabial consonants and voiced plosives on a Pokémon attribute known as friendship. Friendship is a mechanic in the core series of Pokémon video games that is supposed to reflect how the video game characters feel towards the player’s character. This study explores sound symbolic relationships between the sounds that make up the names of Pokémon and their default level of friendship. Many of the previously known cases of cross-linguistic sound symbolic patterns can be explained by the relationship between how sounds in words are articulated and the physical qualities of the referents. This study, however, builds upon the underexplored relationship between sound symbolism and abstract qualities. It shows that bilabial plosives typically represent high friendship values in Pokémon names while /m/, /d/, and /g/ typically represent low friendship values.